Experiences of Adolescent Daughters in Beginning to Live With Their Mothers' Cancer: A Qualitative Study. (May 2023) - Fujimoto, Keiko; Kanda, Kiyoko
This study reveals the experiences of adolescent daughters who are beginning to live with their mothers' cancer diagnosis. Participants were 14 adolescent daughters who were either junior or senior high school students when their mothers were diagnosed with breast cancer. We analyzed semi-structured interviews using content analysis. Using interview data, four categories were created from 23 subcategories and 183 codes: (1) using trial and error to attempt to steady their minds against upset and anxiety; (2) minimizing the effect on their own school life and future; (3) moving forward with the help and support of those around them; and (4) advancing together with their family to protect and take care of their mother. As supporters, we must understand adolescent daughters' experiences in living with their mothers' cancer. Open communication with an important outside individual is essential in promoting adolescent daughters' ability to obtain support and live with their mothers' cancer.